2017
DOI: 10.1063/1.4984054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrical properties and crystallization of indium oxide thin films using ex-situ grazing-incidence wide-angle x-ray scattering

Abstract: Grazing-incidence, wide-angle x-ray scattering measurements were conducted on indium oxide thin films grown on silica substrates via pulsed laser deposition. Growth temperatures (TG) in this study ranged from −50 °C to 600 °C, in order to investigate the thermal effects on the film structure and its spatial homogeneity, as well as their relationship to electrical properties. Films grown below room temperature were amorphous, while films prepared at TG = 25 °C and above crystallized in the cubic bixbyite struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Generally, the peak intensity of C(222) for ALD-deposited In 2 O 3 films increases with the deposition temperature because <111> facet is the most stable state with higher atomic density and lower surface free energy than the other facets such as <110> and <100>. , Our group reported that higher deposition temperature of In 2 O 3 for ALD method enhancing the electrical and film properties such as mobility, film density, and surface roughness because (222) dominant films have fewer defect sites and higher atomic density. , However, the C(222) peak intensity of In 2 O 3 deposited above 300 °C decreases, whereas those for other planes such as (046) increase with the deposition temperature increase (Figures c and S4). This result indicates that ALD-deposited In 2 O 3 films also become polycrystalline structures at high deposition temperatures, as reported for the pulsed layer deposition (PLD) and spraying solution method. , …”
supporting
confidence: 73%
See 1 more Smart Citation
“…Generally, the peak intensity of C(222) for ALD-deposited In 2 O 3 films increases with the deposition temperature because <111> facet is the most stable state with higher atomic density and lower surface free energy than the other facets such as <110> and <100>. , Our group reported that higher deposition temperature of In 2 O 3 for ALD method enhancing the electrical and film properties such as mobility, film density, and surface roughness because (222) dominant films have fewer defect sites and higher atomic density. , However, the C(222) peak intensity of In 2 O 3 deposited above 300 °C decreases, whereas those for other planes such as (046) increase with the deposition temperature increase (Figures c and S4). This result indicates that ALD-deposited In 2 O 3 films also become polycrystalline structures at high deposition temperatures, as reported for the pulsed layer deposition (PLD) and spraying solution method. , …”
supporting
confidence: 73%
“…This result indicates that ALDdeposited In 2 O 3 films also become polycrystalline structures at high deposition temperatures, as reported for the pulsed layer deposition (PLD) and spraying solution method. 39,40 A cross-sectional high-resolution transmission electron microscopy (HRTEM) image and fast-Fourier-transform (FFT) pattern of the In 2 O 3 films near the critical thickness is exhibited in Figure 2. The 250 °C deposited 2 nm thick In 2 O 3 films show an amorphous phase (Figure 2a).…”
mentioning
confidence: 99%
“…The strongest peak is at 2.22 Å À1 corresponding to the (222) plane of the cubic oxide phase. 34,35 The crystallites are randomly oriented and lack texture. Noticeable diffuse spots in the 2D patterns are the diffuse scattering from the silicon (substrate).…”
Section: Resultsmentioning
confidence: 99%